Innovations financières et stabilité du system financier : le cas des crédits default swap (CDS). - Bennamoun, Hamadou (Journal of Human Sciences, 2016)
Credits default swaps (CDS) are financial innovations that have experienced a fuliginous development since their appearance for the first time in 1997; they are used in the transfer of credit risks especially in bonds markets, and more recently in the process of synthetic securitization. Located equally between insurance and financial product, the CDS are negotiated hedging contracts using as underlying a portfolio of loans or bonds, and negotiated by Monoline in an unorganized market.The CDS are considered by experts as one of the main aggravating factors of the subprime crisis (2007) and the global financial crisis (2008) that has followed. These same innovative financial products have been widely used by speculators during the crisis of Greek Sovereign Debt (2010), which contributed to a wide spreading crisis to other EU countries and gave it in the process its systemic character. The pernicious effect of unnecessary financial innovations on the stability of the financial system has been set forth by many researchers, including the precursor Hyman Minsky (1992).